Efisiensi Penggunaan Gambar dalam Pembelajaran Mufrodat Bahasa Arab - Maulida, Anissa Nur (Maliki Interdisciplinary Journal, 2025)
The problems in learning vocabulary for teachers are very complex. This is caused by several factors, one of which is the lack of understanding and creativity of a teacher in teaching. A teacher can find an effective way to convey the knowledge he has and can also choose the right media to facilitate the vocabulary learning process. Media that can be used by teachers include visual media. This media aims to help introduce and teach vocabulary to students. Visual media is very helpful for students in the learning process, because it allows students to freely express and bring out all the creativity and talents that exist within themselves.